“ISTHMOCELE”: Current Perspectives - Dasari, Papa (New Frontiers in Medicine and Medical Research Vol. 13, 2021)
“Isthmocele” or ‘Uterine Diverticulum” or “Uterine Niche” is being increasingly reported during the past three decades and it’s incidence is rising with the rising incidence of Caesarean section. Gynaecological as well as Obstetrical morbidities are reported due to its presence and it is often missed when pregnancy occurs and thus can be” a maternal near miss” or can lead to maternal mortality. Gynecological morbidity is mostly in the form of abnormal uterine bleeding, secondary infertility, new onset dysmenorrhea and chronic pelvic pain. High index of suspicion is important for diagnosis and it can only be diagnosed by imaging such as USG and MRI and the criteria are well defined in recent literature. Management involves repair after exicision of isthmocele laparoscopically or hysteroscopically or by combined route and very rarely hysterectomy is needed to save maternal life in cases of caesarean scar ectopic in shock when encountered as a surprise. This is an iatrogenic condition due to caesarean section and thus it is preventable when adequate precautions are taken during caesarean section in the techniques of incision and suturing and correction of risk factors.